EFFECTIVENESS OF USE ARTIFICIAL INTELLIGENCE IN THE FORM OF CANVA IN DESIGNING TEACHER LEARNING TOOLS IN SCHOOLS - Susilawati, Anggi; Zulkhairi, Zulkhairi; Meutiawati, Ida (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2024)
Artificial Intelligence is artificial intelligence with various types of presentation, one of which is Canva. Canva presents various interesting features that can be used to improve teachers' abilities in creating learning tools for students. The aim of this research is to see the effectiveness of use artificial intelligence in the form of Canva in designing teacher learning tools in schools. This research uses a qualitative descriptive type of research, with a sample of 10 teachers from various subjects. Data analysis used in this research uses descriptive analysis. The results obtained in this research show that the average teacher skill in designing learning tools before using Canva was 56 and after using Canva it was 87. Meanwhile, the teacher skill assessment in designing learning tools before using Canva was 49.4 and after using Canva it was 81.6. So it can be concluded that Usage Artificial Intelligence In the form of Canva in designing learning tools for teachers in schools, it is very effective to use.